P.S. I love you - Ahern, Cecelia (Harper, 2007)
Some people wait their whole lives to find their soul mates. But not Holly and Gerry. They were childhood sweethearts - no one could imagine Holly and Gerry without each other. Until the unthinkable happens. Gerry's death devastates Holly. But as her 30th birthday looms Holly discovers that Gerry has left her a bundle of notes, gently guiding her into her new life without him, each signed 'PS, I Love You'. With some help from her friends, and her noisy and loving family, Holly finds herself laughing, crying, singing, dancing - and being than ever before. Life is for living, she realises - but it always helps if there's an angel watching over you.